OsTTG1, a WD40 repeat gene, regulates anthocyanin biosynthesis in rice. (14th May 2021) - Yang, Xinghai; Wang, Junrui; Xia, Xiuzhong; Zhang, Zongqiong; He, Jie; Nong, Baoxuan; Luo, Tongping; Feng, Rui; Wu, Yanyan; Pan, Yinghua; Xiong, Faqian; Zeng, Yu; et al.
Summary: Anthocyanins play an important role in the growth of plants, and are beneficial to human health. In plants, the MYB‐bHLH‐WD40 (MBW) complex activates the genes for anthocyanin biosynthesis. However, in rice, the WD40 regulators remain to be conclusively identified. Here, a crucial anthocyanin biosynthesis gene was fine mapped to a 43.4‐kb genomic region on chromosome 2, and a WD40 gene OsTTG1 ( Oryza sativa TRANSPARENT TESTA GLABRA1 ) was identified as ideal candidate gene. Subsequently, a homozygous mutant ( osttg1 ) generated by CRISPR/Cas9 showed significantly decreased anthocyanin accumulation in various rice organs. OsTTG1 was highly expressed in various rice tissues after germination, and it was affected by light and temperature. OsTTG1 protein was localized to the nucleus, and can physically interact with Kala4, OsC1, OsDFR and Rc. Furthermore, a total of 59 hub transcription factor genes might affect rice anthocyanin biosynthesis, and LOC_Os01g28680 and LOC_Os02g32430 could have functional redundancy with OsTTG1 . Phylogenetic analysis indicated that directional selection has driven the evolutionary divergence of the indica and japonica OsTTG1 alleles. Our results suggest that OsTTG1 is a vital regulator of anthocyanin biosynthesis, and an important gene resource for the genetic engineering of anthocyanin biosynthesis in rice and other plants. Significance Statement: Anthocyanins have an important health care effect on human health. Thus, it is very important to explore the biosynthesis of anthocyanins in rice. We reported the map‐based cloning and characterization of OsTTG1, a key gene that regulates the anthocyanin biosynthesis in various rice organs. Our findings provide an understanding of the regulation of the plant anthocyanin biosynthesis.